The demographics of developmental hip dysplasia in the Midwestern United States (Indiana). (February 2015) - Loder, Randall T.; Shafer, Cody
Background: Today's society is much more mobile than in the past. This increased mobility has resulted in different marriage/parenting groups. We wished to study the demographics of developmental dysplasia of the hip (DDH) in our area and compare/contrast our findings with those in the literature and specifically look for new findings compared to previous studies. Methods: A retrospective review of all children with DDH from 2003 through 2012 was performed. The age at first visit, gestational age, pregnancy number, gender, race, and family history of DDH was collected. Statistical significance was a p -value < 0.05. Results: There were 424 children (363 girls, 61 boys). Ethnicity was White in 80.8 %, Hispanic in 13.8 %, Black in 4.0 %, and Indo-Malay and Indo-Mediterranean in 0.7 % each; 66.8 % were unilateral; 14.2 % had a positive family history. The average gestational age was 38.1 weeks; 94.4 % were full term. The child was vertex presentation in 67.6 % and breech in 32.4 %; 52.8 % were delivered vaginally and 47.2 % by Cesarean section. The child was the first-born in 48.3 %. When compared to the birth statistics of our state, there was a higher proportion of Whites and Hispanics with DDH, and a lower, but not inconsequential, proportion of Blacks ( p = 0.0018). Conclusion: Mixing of gene pools and infant carrying methods (lack of swaddling or marked abduction) occurring with societal change likely explains the higher than expected proportion of DDH amongst those of Hispanic ethnicity and a lower than expected, but not rare, proportion in those of African ancestry. Level of evidence: Level IV—retrospective case series.